Energy Band Transition and Voltage Compensation via Surface Stoichiometry Alteration in p‐Type Dye‐Sensitized Solar Cells. Issue 10 (14th September 2017) - Xin, Chenghao; Wang, Yu; Zhang, Shicong; Xu, Liang; Yu, Ying; Xiang, Huaide; Wu, Wenjun; Hua, Jianli
Abstract : To fundamentally ameliorate the photovoltaic performances of dye‐sensitized solar cells (DSSCs), p‐type DSSCs (p‐DSSCs) have attracted considerable attention over the last two decades. Herein, by means of a modification with a Ni(NO3 )2 aqueous solution, the stoichiometry of Ni atoms on the surface of a NiO electrode markedly increased. As a result of the change in donor ability and built‐in electric field, the quasi‐Fermi level and the valence band of the semiconductor were greatly reduced, thus effectively improving the open‐circuit voltage of the NiO‐film‐based photovoltaic device. In addition, the increased short‐circuit current density was attributed to the change of the surface distribution state of the sensitizer. Consequently, the power conversion efficiency of the photovoltaic device based on the Ni‐salt‐modified electrode increased by 35.7% from 0.14 to 0.19% compared to that of the plain electrode. This method opens a new strategy to improve the photovoltaic efficiencies of p‐DSSCs. Abstract : For NiO semiconductor, different stoichiometries of the surface Ni and O atoms change the Fermi level and valence‐band energy markedly, which determines the open‐circuit voltage of p‐type dye‐sensitized solar cells (p‐DSSCs) with a fixed redox couple. This method provides a new approach for the customization of the interface behavior, quasi‐Fermi level, and valence‐band position of p‐DSSCs.